2023
DOI: 10.1002/ece3.10249
|View full text |Cite
|
Sign up to set email alerts
|

Nontarget catches of traps with chemical lures may refer to the flower‐visitation, probable pollination, and feeding of bush crickets (Ensifera: Tettigoniidae)

Abstract: The diurnal bees, lepidopterans, and other pollinators are among the most studied flower-visiting insect taxa. They mostly play distinct functions in temperate grasslands and ecotones of grassland-forest mosaics (such as in forest steppes). Although orthopterans are widely distributed in these habitats, however, their flower visitation is nearly unknown, especially in the temperate zone. During the development of traps with chemical lures to catch Lepidoptera pests, large numbers of Orthoptera were caught that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…Traps baited with different volatiles worked in Velyka Dobron' (West Ukraine: Transcarpathia) attracted a large number of seven Tettigonidae species, and five of them showed significant preferences to the tested volatiles: Ruspolia nitidula (Scopoli, 1786), Phaneroptera falcata (Poda, 1761), Leptophyes albovittata (Kollar, 1833), Conocephalus discolor (Thunberg, 1815) and Meconema thallasinum (De Geer, 1773). Since P. falcata and L. albovittata were attracted mainly to compounds included also in different flowers, such as Cirsium, Eupatorium, Achilea, Helianthus and Senecio species, thus it may refer to the host plant preference and flower-visiting habit of these species (Nagy et al 2023). The results are supported by former results on flower-visiting and pollination of tropical Phaneroptera brevis (Tan et al 2017b(Tan et al , 2018aTan and Tan 2017, b).…”
Section: Preliminary Data On Temperate Zone Speciessupporting
confidence: 68%
See 1 more Smart Citation
“…Traps baited with different volatiles worked in Velyka Dobron' (West Ukraine: Transcarpathia) attracted a large number of seven Tettigonidae species, and five of them showed significant preferences to the tested volatiles: Ruspolia nitidula (Scopoli, 1786), Phaneroptera falcata (Poda, 1761), Leptophyes albovittata (Kollar, 1833), Conocephalus discolor (Thunberg, 1815) and Meconema thallasinum (De Geer, 1773). Since P. falcata and L. albovittata were attracted mainly to compounds included also in different flowers, such as Cirsium, Eupatorium, Achilea, Helianthus and Senecio species, thus it may refer to the host plant preference and flower-visiting habit of these species (Nagy et al 2023). The results are supported by former results on flower-visiting and pollination of tropical Phaneroptera brevis (Tan et al 2017b(Tan et al , 2018aTan and Tan 2017, b).…”
Section: Preliminary Data On Temperate Zone Speciessupporting
confidence: 68%
“…In the case of Central Europe, regarding published data and our preliminary results (Nagy et al 2023), study on flower-visiting of Tettigonoidea and Grylloidea species, especially species belonging to genera of Phaneroptera, Leptophyes, Conocephalus, Meconema, Poecilimon and Isophya can be suggested.…”
Section: Discussionmentioning
confidence: 85%
“…Since the composition of the SBL is similar to that of fermenting liquids, its attractivity showed that these fly families prefer damaged parts or leaking sap of different plants. In other cases, this kind of volatile preference is characteristic for species living in forests and forest edges [ 21 , 26 , 28 , 43 ].…”
Section: Discussionmentioning
confidence: 99%